Cover image. (31st October 2020) - Chen, Weizhu; Huang, Yulin; Jiang, Shui; Chen, Gaole; Liu, Yuan
Abstract : The cover image is based on the Original Article Research on sensing characteristics of three human umami receptors via receptor‐based biosensor by Weizhu Chen et al., https://doi.org/10.1002/ffj.3608 .